GANGGUAN PENGHIDU SEBAGAI FAKTOR RISIKO PENURUNAN FUNGSI KOGNITIF PADA LANSIA PENDIDIKAN RENDAH - Yuda Turana* (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION OLFACTORY FUNCTION PLAYS A ROLE IN COGNITIVE DECLINE OLFACTORY DISORDERS ARE KNOWN TO PREDICT FASTER COGNITIVE DECLINE AND INDICATE NERVE DEGENERATION IN THE BRAIN ELDERLY PEOPLE WITH LOWER ASSESSMENT OF OLFACTORY FUNCTION ARE ASSOCIATED WITH DECREASED MEMORY FUNCTION WHILE THE ELDERLY WITH LOW EDUCATION ARE KNOWN TO HAVE A HIGH RISK OF DEVELOPING DEMENTIA SO FAR THERE HAS BEEN NO RESEARCH ON DISORDERS OF OLFACTORY ON COGNITIVE FUNCTION OF ELDERLY WITH LOW EDUCATION